Extending the Family of V4+S= 1/2 Kagome Antiferromagnets. Issue 51 (30th October 2015) - Clark, Lucy; Aidoudi, Farida H.; Black, Cameron; Arachchige, Kasun S. A.; Slawin, Alexandra M. Z.; Morris, Russell E.; Lightfoot, Philip
Abstract: The ionothermal synthesis, structure, and magnetic susceptibility of a novel inorganic–organic hybrid material, imidazolium vanadium(III, IV) oxyfluoride [C3 H5 N2 ][V9 O6 F24 (H2 O)2 ] (ImVOF) are presented. The structure consists of inorganic vanadium oxyfluoride slabs with kagome layers of V 4+ S = 1/2 ions separated by a mixed valence layer. These inorganic slabs are intercalated with imidazolium cations. Quinuclidinium (Q) and pyrazinium (Pyz) cations can also be incorporated into the hybrid structure type to give QVOF and PyzVOF analogues, respectively. The highly frustrated topology of the inorganic slabs, along with the quantum nature of the magnetism associated with V 4+, means that these materials are excellent candidates to host exotic magnetic ground states, such as the highly sought quantum spin liquid. Magnetic susceptibility measurements of all samples suggest an absence of conventional long‐range magnetic order down to 2 K despite considerable antiferromagnetic exchange. Abstract : All in a spin : Antiferromagnetic crystalline solids with a kagome network of ions are desired as realizations of two‐dimensional quantum spin liquids. Until recently, the few examples of these materials were all based on Cu 2+ ions. Now, the ionothermal synthesis, structure, and magnetic properties of a family of inorganic–organic hybrid solids that contain antiferromagnetic kagome layers of V 4+ ions is presented.